2022
DOI: 10.1111/petr.14440
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23‐Klotho and mineral metabolism in the first year after pediatric kidney transplantation: A single‐center prospective study

Abstract: Background:The role of fibroblast growth factor 23 (FGF23) levels in mineral metabolism before and after kidney transplantation in pediatric patients is poorly understood. Methods:We prospectively evaluated 24 patients under 18 years of age (4.5 [3.3-9.8] years) who underwent living kidney transplantation between July 2016 and March 2018, and measured intact FGF23 and serum αKlotho levels, and other parameters of mineral metabolism before and after transplantation (Day 7, 1 and 4 months, and 1 year). Relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“… 42 One study showed that Klotho levels 7 d and 1 mo posttransplant were similar to Klotho levels before transplantation, but levels started to rise approximately 4 mo posttransplant. 45 Another study on long-term surviving kidney transplant recipients (>10 y after transplantation) showed a nonsignificant decline in Klotho levels 43 ; this might be as expected from 10 y of aging.…”
Section: Discussionmentioning
confidence: 89%
“… 42 One study showed that Klotho levels 7 d and 1 mo posttransplant were similar to Klotho levels before transplantation, but levels started to rise approximately 4 mo posttransplant. 45 Another study on long-term surviving kidney transplant recipients (>10 y after transplantation) showed a nonsignificant decline in Klotho levels 43 ; this might be as expected from 10 y of aging.…”
Section: Discussionmentioning
confidence: 89%
“…The FGF23 gene is a member of a large family of fibroblast growth factors [94], which is most associated with the KLOTHO gene in anti-aging processes [95]. A number of publications have examined the relationship of FGF23 and KLOTHO genes in physiological processes and in various diseases [96][97][98][99][100][101][102][103][104]. In this regard, we studied the possible effect of piRNA on the expression of the FGF23 gene.…”
Section: Resultsmentioning
confidence: 99%